(untitled) (Economic studies journal, 2021)
Abstract This study aimed to identify the obstacles that hinder the implementation of Islamic banks in Libya an achieve the goal of the study, and this study adopted the modern scientific method or the deductive and inductive method. The study also adopted the questionnaire as the main tool for data collection, and the study population represented the supervisory department in the management of branches in the eastern region, bank managers, heads of departments and legal auditors of commercial banks in the city of Benghazi (AL- Wahda bank, AL- Jumhuriya bank and EL- Tyjari Watani bank). 40 questionnaires were distributed and 35 of them were returned valid for analysis. The study used the statistical method represented in Cronbach’s alpha test for validity and reliability, and the one sample T- test and ANOVA were used to test the study’s hypotheses. The results of the study concluded that there is a shortage of scientifically and legally qualified human cadres that constitute and obstacle to the success of the application of Islamic banks in Libya, as well as the absence of special department of Islamic banking work and also the lack of clarity of the financial and legal control procedures related to the work of Islamic banks as the results of the study concluded that there is no organizational structure that takes into account the investment, social and Islamic bank financial market.